(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
This article describes the hazards and causes of VOCs as well as the state of VOCs. It is the main culprit in the production of VOCs, which is the main culprit of the production of VOCs source materials in automobile, and analyzes the production of VOCs in the raw material production process from the source. Finally, proposed reduction measures from three aspects of the raw materials, production, management.